Information communication and its role in pedagogical communication and cooperation - Oseredchuk, Olha; Hloba, Lidiia; Apshay, Fedir; Shyp, Oksana; Andriiv, Nataliia M. (Linguistics and Culture Review, 2021)
The purpose of the article is to develop a model of the organization of information communications within the pedagogical process. The leading method for the study of this problem was testing developed by M.V. Matyukhina to study the motivational component of students with the identification of its main parameters, which allow us to determine the parameters for creating conditions to improve the educational process and increase the interest of students to it. The identified indicators while using technical equipment have allowed the creation of a model of organization of the development of information communications to significantly deepen and improve the educational process in the pedagogical environment by including a friendly form of communication at the level of different universities, schools with the establishment of international relations, which will facilitate the exchange of knowledge and experience, and create conditions to improve the intellectual and cultural sphere through classes and lectures by teachers from different countries, as well as joint holding and dialogue of subject classes of appropriate age group of schoolchildren and students with their peers from other countries based on online inclusion on the blackboard-size TV screen, which will create an environment presence and has good technical characteristics.